2010
DOI: 10.1055/s-0030-1255524
|View full text |Cite
|
Sign up to set email alerts
|

Histologic diagnosis based on forceps biopsy is not adequate for determining endoscopic treatment of gastric adenomatous lesions

Abstract: We should consider endoscopic resection for gastric LGD that are 2 cm or more in size and do not have whitish discoloration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 8 publications
8
76
0
Order By: Relevance
“…They reported that a lesion size C2 cm, the presence of erythema, or depressed lesions were significantly associated with an upgraded histology, consistent with previous Korean studies reporting that EGC diagnosed initially with endoscopic biopsy can be underdiagnosed as LGD [2][3][4][5]. Yet, in Japan, where the term ''adenoma with low-grade atypia'' is used to describe a lesion, concerns might be raised about the endoscopic resection of adenomas with LGD.…”
supporting
confidence: 67%
“…They reported that a lesion size C2 cm, the presence of erythema, or depressed lesions were significantly associated with an upgraded histology, consistent with previous Korean studies reporting that EGC diagnosed initially with endoscopic biopsy can be underdiagnosed as LGD [2][3][4][5]. Yet, in Japan, where the term ''adenoma with low-grade atypia'' is used to describe a lesion, concerns might be raised about the endoscopic resection of adenomas with LGD.…”
supporting
confidence: 67%
“…The histology of pre-treatment forceps biopsy samples does not always accurately identify malignancies, while tissue from endoscopic resection (ER) tends to yield a more accurate histological diagnosis. The discrepancy rate between forceps biopsy and ER has ranged from about 20 to 45% [5][6][7]. This discrepancy calls into question the accuracy of forceps biopsy in differentiating adenomas from cancerous lesions.…”
Section: Discussionmentioning
confidence: 99%
“…In non-magnifying endoscopy, lesion size, color (red or white), macroscopic type of the lesion (depressed or others), and the presence of ulceration were examined, based on the past reports about the association between endoscopic findings and histological malignancy [6,17,20,21]. Lesion size was determined using a measuring forceps.…”
Section: Endoscopic Procedures and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In 20-40 % of cases, diagnostic discrepancy between dysplasia evident at biopsy and GC observed in the resection specimen has been reported [34,37,44]. In most cases, the lesions were thought to be cancer at the time of initial biopsy [1,[44][45][46][47]. From a Western point of view, the final diagnosis rests on examination of the surgical or ESD specimen, because there is some possibility of cancer even if the diagnosis is LGD or HGD [21,23,36,[46][47][48].…”
Section: Discussionmentioning
confidence: 99%